Time as a factor in the identification of subjects with different susceptibility to plaqueinduced gingivitis - Leonardo Trombelli (journal of clinical periodontology, 2006)
Objectives: The purpose of this study was to assess whether identification of subjects with different susceptibility to plaque-induced gingival inflammation is dependent on the length of time of de novo plaque accumulation. Methods: Retrospective analysis of data obtained from a recently reported (J Clin Periodontol 31, 239, 2004) randomized split-mouth localized experimental gingivitis trial involving 96 healthy non-smokers. Gingival and plaque index, gingival crevicular fluid volume (GCF), angulated bleeding score, and the derived parameter cumulative plaque exposure (CPE) were recorded at days 0, 7, 14, and 21. The primary outcome variable to express severity of inflammation was GCF and each subject was a statistical unit. Based on subject distribution of GCF-day 21 residuals after standardization for CPE-day 21, two sub-populations (upper and lower distribution quartiles) were selected. They were, respectively, defined as ‘‘high responders’’ (HR) (n524) and ‘‘low responders’’ (LR) (n524) and characterized by significantly different severity of gingivitis to similar amounts of plaque deposits. The same analysis was repeated at days 7 and 14. Prevalence of HR and LR was compared between days using the w2 [ML] test. Results: For both day 7 and day 14, the quartile distribution of LR and HR was statistically significant (p50.02). Fifty percent of LR and 71% of HR presented a consistent level of susceptibility to plaque-induced gingival inflammation even after only 7 and/or 14 days of plaque accumulation. Conclusions: These findings support the concept that the subject-based susceptibility to plaque-induced gingival inflammation is an individual trait, only partly related to the length of time of exposure to plaque.